URGENSI TEORI PRODUKSI DAN PERILAKU PRODUSEN DALAM PERSPEKTIF ISLAM - Hamzah Kamma (MUAMALAH, 2015)
The production is a process that has been born on this earth since humans inhabit this planet. Production very principle for the survival of human civilization and the earth. Production, distribution and consumption of the circuit is actually an economy that can not be separated. There are differences between conventional economists with Islamic economists in discussions about the production. While the capitalist understanding, which currently controls the world, looking at capital or capital as the most important element. Islam wants to put him in the right position, ie all that in order to maximize the satisfaction and benefit the world and the hereafter. Production activities is a chain of consumption and distribution. Produksilah activities that produce goods and services, then consumed by consumers. Without production, the economic activity will stop, and vice versa. To produce goods and services production activities involve a lot of factors of production. The production function describes the relationship between the amount of input to output that can be generated in a given period of time. In production theory provides an explanation of the behavior of producers to maximize profits and optimize the efficiency of its production. Where Islam recognizes private property within certain limits, including ownership of the means of production, but this right is not absolute